2012
DOI: 10.1155/2012/690362
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Glucose Control in Neurosurgical Patients

Abstract: Many neurosurgery patients may have unrecognized diabetes or may develop stress-related hyperglycemia in the perioperative period. Diabetes patients have a higher perioperative risk of complications and have longer hospital stays than individuals without diabetes. Maintenance of euglycemia using intensive insulin therapy (IIT) continues to be investigated as a therapeutic tool to decrease morbidity and mortality associated with derangements in glucose metabolism due to surgery. Suboptimal perioperative glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 94 publications
0
21
0
1
Order By: Relevance
“…8,9 However, the extent to which chronic opioid use independently influences surgical outcomes remains poorly understood. In this context, we sought to define the differences in healthcare utilization and associated costs among patients undergoing elective abdominal surgical procedures in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, the extent to which chronic opioid use independently influences surgical outcomes remains poorly understood. In this context, we sought to define the differences in healthcare utilization and associated costs among patients undergoing elective abdominal surgical procedures in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies showed increased morbidity and mortality with hyperglycemia, after coronary artery bypass grafting (7-8). Diabetes is a well-known risk factor for postoperative infections (9), acute renal failure, ileus and prolonged hospital stay (10)(11). These data show the importance of perioperative blood glucose control in diabetes.…”
Section: Hyperglycemia and Perioperative Adverse Eventsmentioning
confidence: 92%
“…Factors such as trauma, hemorrhage, ischemia, infection, surgery stress, anesthetic agents, critical illness and metabolic stress may lead to insulin resistance and B-cell dysfunction. These factors may cause the increase in blood glucose [12]. The stress of surgery may be the main factor.…”
Section: Fluctuations Of Blood Glucose During the Perioperative Periomentioning
confidence: 99%
“…Stress also evokes the development of insulin resistance, which can be caused by proinflammatory cytokines [13,14] and other factors such as some drugs. Stress-induced hyperglycemia may induce endothelial cell dysfunction, defects in immune function, aggravated oxidative stress, prothrombotic changes, cardiovascular effects, and specific brain area injury or a direct hypothalamic damage/irritation of glucose regulatory centers [12,[15][16][17]. Hyperglycemia has been shown to exasperate these deleterious effects.…”
Section: Fluctuations Of Blood Glucose During the Perioperative Periomentioning
confidence: 99%
See 1 more Smart Citation